2020
DOI: 10.1111/1541-4337.12677
|View full text |Cite
|
Sign up to set email alerts
|

Starch‐based nanoparticles: Stimuli responsiveness, toxicity, and interactions with food components

Abstract: In recent years, starch‐based nanoparticles have attracted great interest due to their small size, good biocompatibility, and environmental friendliness, as well as their potential applications in foods, drug delivery carriers, and biodegradable edible films. Compared with nonstarch polysaccharides, starch can be enzymatically hydrolyzed into glucose in vivo, so it can be used as an enzyme‐responsive carrier. The recent research progress of starch‐based nanoparticles, including starch nanoparticles, starch nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 158 publications
(224 reference statements)
1
20
0
Order By: Relevance
“…In assessing the gel properties, pharmacokinetics, morphology, anticancer activity and immunohistopathology after thermosensitive irinotecan-encapsulated solid lipid nanoparticles (SLN) rectal administration to tumor-bearing mice, it was easily administered to the anus, gelling rapidly and strongly after rectal administration, inducing no damage to the rat rectum and no body weight loss in tumor-bearing mice ( 135 ). Futhermore, mutiple nanocarrier, including bio-nanocapsule-liposome nanocarrier ( 136 ), poly{(benzyl-L-aspartate)-co-[N-(3-aminopropyl) imidazole-L-aspartamide]}-poly(ethylene glycol) ( 137 ), Polysaccharide-based nanocarriers ( 138 ), ( 139 ), Poly(aspartic acid-graft-imidazole)-poly(ethylene glycol) [P(Asp-g-Im)-PEG] ( 140 ), amphiphilic copolymer of poly(epsilon-caprolactone)-b-poly(ethylene glycol)-b- poly(epsilon-caprolactone) ( 141 ), were demonstrated to be safety in vivo in treatment cancer, inflammatory bowel disease. Additionally, some material was demonstrated to be safety such as starch-based nanoparticles ( 139 ).…”
Section: Safety Of Nanocarriersmentioning
confidence: 99%
“…In assessing the gel properties, pharmacokinetics, morphology, anticancer activity and immunohistopathology after thermosensitive irinotecan-encapsulated solid lipid nanoparticles (SLN) rectal administration to tumor-bearing mice, it was easily administered to the anus, gelling rapidly and strongly after rectal administration, inducing no damage to the rat rectum and no body weight loss in tumor-bearing mice ( 135 ). Futhermore, mutiple nanocarrier, including bio-nanocapsule-liposome nanocarrier ( 136 ), poly{(benzyl-L-aspartate)-co-[N-(3-aminopropyl) imidazole-L-aspartamide]}-poly(ethylene glycol) ( 137 ), Polysaccharide-based nanocarriers ( 138 ), ( 139 ), Poly(aspartic acid-graft-imidazole)-poly(ethylene glycol) [P(Asp-g-Im)-PEG] ( 140 ), amphiphilic copolymer of poly(epsilon-caprolactone)-b-poly(ethylene glycol)-b- poly(epsilon-caprolactone) ( 141 ), were demonstrated to be safety in vivo in treatment cancer, inflammatory bowel disease. Additionally, some material was demonstrated to be safety such as starch-based nanoparticles ( 139 ).…”
Section: Safety Of Nanocarriersmentioning
confidence: 99%
“…Antimicrobial packaging is another promising area of the food industry that has received growing attention [110]. Starchbased nanoparticles display unique properties, such as controllable release, improved water solubility, bioavailability, and improved delivery of active ingredients in foods and within the human body [111,112]. In addition to enhancing the properties of starch films, starch-based nanoparticles can be used to produce high value-added products, such as the biodegradable carriers for drug delivery [113].…”
Section: Value-added Products From Sweet Potato Starchmentioning
confidence: 99%
“…Starch-based nanoparticles with desired sizes can be produced using amylases or/and debranching enzymes to digest the α-1,4-glucosidic or α-1,6-glucosidic bonds in starch. Enzymatic hydrolysis is likely to yield homogeneous nanoparticles when the starch contains more A and B type short chains with an average DP of 14-18 [112]. Sun et al reported a method of producing starch granules of 60-120 nm in size from maize waxy starch that has 99% amylopectin [114].…”
Section: Value-added Products From Sweet Potato Starchmentioning
confidence: 99%
“…Bio‐responsive (bio‐decomposable) polymeric assemblies have attracted attention in, e.g., drug and gene delivery, tissue engineering, and bioimaging applications. [ 21–24 ] A possible advantage of use of polymeric (diblock or triblock) assemblies is prolonged circulation of drugs in the body. In the present paper, bio‐decomposable assemblies mean assemblies that can decompose in biological conditions because either a part of the polymer or the entire polymer is biodegradable.…”
Section: Introductionmentioning
confidence: 99%